A novel approach with tofacitinib for the management of keratoderma blennorrhagicum in reactive arthritis: a case report - Maitiyaer, Maierhaba; Liu, Yu; Keyimu, Nueramina; Wen, Yueqiang; Liu, Zhiping; Huang, Wenhui; Yu, Shuilian (Frontiers in Immunology, 2024)
Reactive arthritis(ReA), a form of arthritis occurring post-infection, manifests with antecedent infection symptoms, arthritis, and extra-articular manifestations, categorizing it as spondyloarthritis. "Keratoderma blennorrhagicum" (characterized by pustular hyperkeratosis on palms and soles, resembling pustular psoriasis) represents the most typical skin manifestation of ReA, occurring in acute or chronic phases. Severe lesions necessitate systemic disease modifying anti-rheumatic drugs (DMARDs) or biologic therapies. This article reports a case of ReA with sacroiliitis and widespread pustular eruptions following a urinary tract infection. Treatment with sulfasalazine and thalidomide significantly improved sacroiliitis, but the skin rash remained persistent and recurring. Subsequent use of adalimumab and secukinumab resulted in worsening skin rash, prompting a switch to tofacitinib, leading to a remarkable improvement in pustular eruptions after 20 days of treatment. This case demonstrates successful application of tofacitinib in treating severe keratoderma blennorrhagicum refractory to conventional DMARDs and biologics, offering insights into JAK inhibition for challenging rheumatic diseases with skin involvement.